Dynamic Target Tracking Method Based on Medical Imaging - Qin, Guofeng; Qin, Jiahao; Xia, Qiufang; Zou, Jianghuang; Lin, Pengpeng; Ren, Chengkun; Wang, Ruihan (Frontiers in Physiology, 2022)
The cross fusion of rehabilitation medicine and computer graphics is becoming a research hotspot. Due to the problems of low definition and unobvious features of the initial video data of medical images, the initial data is filtered and enhanced by adding image preprocessing, including image rotation and contrast enhancement, in order to improve the performance of the tracking algorithm. For the moving barium meal, the discrete point tracking and improved inter frame difference method are proposed; for the position calibration of tissues and organs, the KCF + dsst correlation filtering method and the corresponding multi-target tracking method are proposed, and the experimental results show that the tracking effect is better. The two algorithms modify each other to further improve the accuracy of calibration and tracking barium meal flow and soft tissue organ motion, and optimize the whole swallowing process of moving target tracking model.